Hubungan Frekuensi Menonton Drama Korea dengan Pemilihan Makanan Remaja Di Balikpapan - Praseptia Gardiarini; Chardina Dianovita; Farida Farida (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2023)
Korean dramas are currently the craze of teenagers, including among students. This allows for behavioral changes due to seeing what is in the drama, one of which is about food selection. This study aims to determine the relationship between the frequency of watching Korean dramas with food choices for students in the Hospitality Department, Poltekba. This study uses a quantitative approach with a cross-sectional study method. Data collection includes demographic data on students such as age, gender, education level and student income. Additional data are the frequency of watching Korean dramas, food selection and a semi-quantitative food frequency questionnaire to obtain student consumption data. The population in this study were Poltekba students with a sample of 79 students. Data analysis method using Pearson correlation. The results of the descriptive data obtained were 83.5% women with an age range of 20-23 years as many as 60.8%, the level of education in the second year was 68% and the dominant income was classified as moderate at 48.1%.. While the results of food selection, students chose snacks and Korean main meals by 40% and 48%, respectively. Based on the Pearson Correlation test, which is equal to p-value 0.018 and p-value 0.015, it proves that there is a significant relationship between the frequency of watching Korean dramas and food choices for Catering students at Poltkba.